CORPORATE GOVERNANCE DAN EFISIENSI BIAYA (BOPO): STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG LISTING DI BEI TAHUN 2020-2024 - Nor Aisah, Siti; Tita Nawangsari, Ajeng (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
This study aims to analyze the effect of Corporate Governance (CG) mechanisms, proxied by the Number of Commissioners, Independent Commissioners, Managerial Ownership, and Institutional Ownership, on Cost Efficiency (BOPO) in commercial banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, while controlling for Company Size and Return on Assets (ROA). The method uses panel data with Random Effect Model (REM) estimation as the best model, after a series of Chow Tests and Hausman Tests. The F-test results show that these variables simultaneously have a significant effect on BOPO (Prob F-statistic) with a model explanatory contribution of (Adjusted R-squared). Partially, all main corporate governance variables do not have a significant effect on BOPO, while the ROA control variable has a negative and significant effect. The implications of these findings support Alignment Theory, emphasizing the importance of external supervision to reduce agency costs and promote banking operational efficiency.